Sizing agent additive with gemini-like structure as well as preparation method and application thereof
By using Gemini-like slurry additives, the problems of large molecular weight, poor compatibility and dispersion of slurry additives in the prior art are solved, efficient dispersion and flexibility of slurry are achieved, and the production process of lithium-ion batteries is improved. and product performance.
Patent Information
- Application Number
- CN202411464431.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-18
AI Technical Summary
The slurry additives of existing lithium-ion batteries have large molecular weight, poor compatibility and dispersion, which affect the flexibility of the slurry and lead to prone to cracking, layering and hard precipitation during the coating process.
Gemini-like structure slurry additives are used, which include a low-polar flexible backbone and a covalent bonded strong polar head group. Multiple flexible backbones are connected through a bridge structure to improve dispersion and flexibility.
It significantly improves the overall dispersion and flexibility of the slurry, reduces the critical micelle concentration, reduces the additive amount, improves the compatibility and processing performance of the slurry, and avoids cracking and stratification problems.
Smart Images

Figure CN119463154A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of lithium-ion battery positive electrode materials, and in particular relates to a twin-structure slurry additive and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are a new generation of green high-energy batteries with excellent performance. They have the characteristics of high voltage, high capacity, low consumption, many cycles, small size, low internal resistance and low self-discharge. Due to the above characteristics, lithium-ion batteries have been applied to many civil and military fields such as mobile phones, laptops, camcorders, digital cameras, etc.
[0003] Lithium-ion batteries are mainly composed of positive electrode slurry, negative electrode slurry, diaphragm and electrolyte. Among them, positive electrode slurry and negative electrode slurry are the main components of lithium-ion batteries and directly affect the performance of lithium-ion batteries. Positive electrode slurry is composed of adhesive, conductive agent, positive electrode material, etc.; negative electrode slurry is composed of adhesive, graphite carbon powder, etc. The preparation of positive and negative electrode slurries includes a series of process processes such as mixing, dissolving and dispersing between liquid and liquid, liquid and solid materials, and this process is accompanied by changes in temperature, viscosity, environment, etc. In the positive and negative electrode slurries, the dispersion and uniformity of the granular active material directly affect the movement of lithium ions between the two poles of the battery. Therefore, the mixing and dispersion of the slurries of various pole sheet materials is crucial in the production of lithium-ion batteries. The quality of slurry dispersion directly affects the quality of subsequent lithium-ion battery production and the performance of its products.
[0004] The traditional preparation process mainly involves adding traditional dispersants, which have large molecular weights, slow migration speeds, and poor compatibility with the main materials in the slurry. Generally speaking, a large amount of dispersants need to be added, and a long homogenization time is required to achieve the dispersion effect. The resulting slurry has poor dispersibility and stability, and is prone to stratification and hard precipitation problems. Due to the large amount of added dispersants, cracking is prone to occur during the coating process, and the flexibility is poor, which affects the processing performance of the slurry and further affects the use of the product. Therefore, it is urgent to provide a new slurry additive for the preparation of lithium-ion batteries. Summary of the invention
[0005] The purpose of the present application is to provide a twin-structure slurry additive and its preparation method and application, aiming to solve the problem in the prior art that the slurry additive for lithium-ion batteries has a large molecular weight, poor compatibility and dispersibility with the main material in the slurry, and affects the flexibility of the slurry.
[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0007] In a first aspect, the present application provides a twin-structure slurry additive, which includes at least one low-polarity flexible main chain and a strong polar head group covalently connected to the flexible main chain, wherein the flexible main chain includes a bridging structure.
[0008] In some embodiments, the flexible backbone comprises a polyether backbone or a polyester backbone.
[0009] In some embodiments, the bridging structure comprises an "NN" bond.
[0010] In some embodiments, when the flexible main chain is a polyether main chain, the twin-structure slurry additive has a structure shown in the following structural formula I:
[0011]
[0012] Wherein, R1 is a C2-C5 alkane, 1-2 units of 1-methyl-2-ethylamine or an ether with 1-4 carbon atoms at both ends; R2 and R2' can be independently selected from any one of a polyethylene glycol structural unit, a polypropylene glycol structural unit, and a mixed unit of polyethylene glycol and polypropylene glycol, m is an integer of 0-20, n is an integer of 0-20, and 5≤m+n≤20; R3 and R3' can be independently selected from H or a C1-C3 alkane; R4 is at least one group selected from the group consisting of -NH2, -NHCO-CH3, -OH, Ar-OH, and -COOH;
[0013] When the flexible main chain is a polyester main chain, the twin-structure slurry additive has a structure shown in the following structural formula II:
[0014]
[0015] Among them, R1 is a C2-C5 alkane, 1-2 units of 1-methyl-2-ethylamine or an ether with 1-4 carbon atoms at both ends; R4 is at least one group selected from the group consisting of -NH2, -NHCO-CH3, -OH, Ar-OH, and -COOH; R5 and R5' can be independently selected from any one of poly(hexylene adipate) structural units, polycarbonate diol structural units, poly(butylene adipate) structural units, and polycaprolactone structural units, and 5≤p≤20, 5≤q≤20, and |pq|≤2; R6 and R6' can be independently selected from H or an alkane chain with 1 to 3 carbon atoms.
[0016] In some embodiments, the weight average molecular weight of the gemini-like structure slurry additive is 1,000 to 3,000.
[0017] In a second aspect, the present application provides a method for preparing a twin-structure slurry additive, comprising the following steps:
[0018] A double-terminal amine compound H2N-R1-NH2 and a flexible polymer compound containing an epoxy terminal group are mixed and subjected to a first ring-opening reaction, followed by purification treatment to prepare a quasi-gemini structure solvated chain; wherein R1 is a C2-C5 alkane, 1-2 units of 1-methyl-2-ethylamine, or an ether having 1-4 carbon atoms at the double terminals;
[0019] A small molecule compound is provided, and the small molecule compound is mixed with a twin-structure solvated chain to perform a second ring-opening reaction, and then a purification treatment is performed to prepare a twin-structure slurry additive, wherein the twin-structure slurry additive includes at least one group selected from the group consisting of -NH2, -NHCO-CH3, -OH, Ar-OH, and -COOH.
[0020] In some embodiments, the flexible polymer compound containing epoxy terminal groups includes a polyether compound containing epoxy terminal groups or a polyester compound containing epoxy terminal groups.
[0021] In some embodiments, the polyether compound containing epoxy terminal groups is R2 and R2' can be independently selected from any one of polyethylene glycol structural units, polypropylene glycol structural units, and mixed units of polyethylene glycol and polypropylene glycol, m is an integer of 0 to 20, and n is an integer of 0 to 20; R3 and R3' can be independently selected from H or C1 to C3 alkanes.
[0022] In some embodiments, the polyester compound containing epoxy end groups is Wherein, R5 and R5' can be independently selected from any one of poly(hexylene adipate) structural unit, polycarbonate diol structural unit, poly(butylene adipate) structural unit and polycaprolactone structural unit, and 5≤p≤20, 5≤q≤20; R6 and R6' can be independently selected from H or an alkane chain of 1 to 3 carbons.
[0023] In some embodiments, the temperature of the first ring-opening reaction is 60-80° C., and the time is 4-8 hours.
[0024] In some embodiments, the temperature of the second ring-opening reaction is 23-25° C., and the time is 3-6 hours.
[0025] In some embodiments, the double-terminal amine compound is selected from ethylenediamine, propylenediamine, diethylenetriamine, and 2,2'-oxybis(ethylamine).
[0026] In some embodiments, the small molecule compound is selected from any one of p-hydroxybenzoic acid, 3,4-dihydroxybenzoic acid, 3,4,5-trihydroxybenzoic acid, acrylamide, acrylamide, propylene oxide, and methyl acrylate.
[0027] In some embodiments, the flexible polymer compound containing epoxy terminal groups is selected from at least one of epoxy terminal polyethylene glycol with a degree of polymerization of 10 to 20, epoxy terminal polypropylene glycol with a degree of polymerization of 10 to 20, poly(hexylene adipate) with a degree of polymerization of 5 to 10, polycarbonate diol, poly(butylene adipate), and polycaprolactone.
[0028] In a third aspect, the present application provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode film layer located on at least one surface of the positive electrode current collector, wherein the positive electrode film layer is obtained by coating a positive electrode slurry, wherein the positive electrode slurry comprises the above-mentioned twin-like structure slurry additive or a positive electrode slurry prepared according to the above-mentioned twin-like structure slurry additive preparation method.
[0029] In a fourth aspect, the present application provides a secondary battery, the secondary battery comprising a positive electrode plate.
[0030] The first aspect of the present application provides a twin-structure slurry additive, which includes at least one low-polarity flexible main chain and a strong polar head group covalently connected to the flexible main chain, wherein the strong polar head group can better adsorb high-polarity components in the slurry, firmly anchor with it, play a role of steric hindrance, and significantly improve the overall dispersibility of the slurry; the low-polarity flexible main chain has good compatibility with the solvent in the slurry, and can form a stable emulsified system, which is conducive to better stabilizing the particles in the slurry and avoiding slurry aggregation and sedimentation. The main chain has excellent flexibility and avoids the problem of cracking when the slurry is thickly coated; and multiple flexible main chains can be connected by a bridging structure. The bridge structure used can prevent the electrostatic repulsion between the polar groups, so that they are more closely arranged on the surface of the slurry particles, thereby reducing the critical micelle concentration, that is, a smaller addition amount can play a better dispersing functional characteristic. This type of twin-structure slurry additive is used in battery slurry, has excellent compatibility with the slurry, is conducive to improving the dispersion effect, and can improve the slurry flexibility, and can be widely used.
[0031] The second aspect of the present application provides a method for preparing a twin-structure slurry additive. The preparation method adopts a two-step process. First, a double-terminal amine compound is used to "bridge" and a flexible polymer compound containing an epoxy end group is subjected to a ring-opening reaction to prepare a bridging flexible twin-structure solvated chain; then the flexible twin-structure solvated chain is chemically reacted with a small molecule compound containing a strong polar head group to prepare a twin-structure slurry additive. The preparation method is simple, the reaction is mild, does not require the use of large-scale instruments and equipment, is low in cost, and is easy to industrialize.
[0032] The third aspect of the present application provides a positive electrode plate, which includes a positive electrode collector and a positive electrode film layer located on at least one surface of the positive electrode collector, wherein the positive electrode film layer is obtained by coating the positive electrode slurry, wherein the above-mentioned twin-structure slurry additive is applied to the positive electrode slurry, which is beneficial to reducing the viscosity of the positive electrode slurry and improving the dispersibility of the positive electrode slurry. At the same time, it can reduce the aggregation of positive electrode active materials in the positive electrode slurry, improve the performance of the positive electrode slurry, and make the obtained positive electrode slurry have good dispersion effect, so that the positive electrode active materials in the positive electrode slurry are evenly dispersed on the surface of the positive electrode plate, and at the same time play the role of preventing cracking, reducing coating time, and improving efficiency.
[0033] A secondary battery provided in the fourth aspect of the present application includes a positive electrode, a negative electrode and an electrolyte, and the provided secondary battery includes the above-mentioned positive electrode plate. The obtained secondary battery has excellent cycle performance and specific capacity, which is conducive to wide application. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0035] Figure 1 This is a finished product picture of the twin-structure slurry additive provided in the embodiment of the present application.
[0036] Figure 2 This is an infrared spectrum analysis chart of the twin-structure slurry additive obtained in Example A1 provided in the examples of the present application.
[0037] Figure 3 It is a graph of 500 cycle data of the secondary batteries of Example B1, Example B6, Comparative Example B2 and Comparative Example B4 of the present application at a current density of 1C. DETAILED DESCRIPTION
[0038] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0039] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0040] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0041] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0042] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0043] The mass of the relevant components mentioned in the specification of the examples of this application can not only refer to the specific content of each component, but also represent the proportional relationship between the masses of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the specification of the examples of this application, it is within the scope disclosed in the specification of the examples of this application. Specifically, the mass in the specification of the examples of this application can be mass units known in the chemical industry such as μg, mg, g, and kg.
[0044] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0045] A first aspect of an embodiment of the present application provides a twin-structure slurry additive, which includes at least one low-polarity flexible main chain and a strong polar head group covalently connected to the flexible main chain, wherein the flexible main chain includes a bridging structure.
[0046] The first aspect of the embodiment of the present application provides a twin-structure slurry additive, which includes at least one low-polarity flexible main chain and a strong polar head group covalently connected to the flexible main chain, wherein the strong polar head group can better adsorb high-polarity components in the slurry, firmly anchor with it, play a role of steric hindrance, and significantly improve the overall dispersibility of the slurry; the low-polarity flexible main chain has good compatibility with the solvent in the slurry, and can form a stable emulsified system, which is conducive to better stabilizing the particles in the slurry and avoiding slurry aggregation and sedimentation. The main chain has excellent flexibility and avoids the problem of cracking when the slurry is thickly coated; and multiple flexible main chains can be connected by a bridging structure. The bridge structure used can prevent the electrostatic repulsion between the polar groups, so that they are more closely arranged on the surface of the slurry particles, thereby reducing the critical micelle concentration, that is, a smaller amount of addition can play a better dispersing functional characteristic. This type of twin-structure slurry additive is used in battery slurry, has excellent compatibility with the slurry, is conducive to improving the dispersion effect, and can improve the slurry flexibility, and can be widely used.
[0047] In some embodiments, the flexible main chain includes a polyether main chain or a polyester main chain. Among them, the polyether main chain contains a large number of oxygen atoms in the polymer, and its molecule contains one or more ether bonds. Since the ether bonds can rotate arbitrarily, the formed polyether main chain has excellent flexibility and good hydrophilicity, which improves the compatibility with the solvent; while the polyester main chain is a high molecular polymer, which is connected by countless ester bonds; the ester bonds also have a certain degree of twistability, so the formed polyester main chain has high flexibility, which is conducive to improving the overall flexibility of the slurry, playing a role in thick coating to prevent cracking while reducing coating energy consumption, improving slurry processability and increasing slurry solid content.
[0048] In some embodiments, the bridging structure includes an "NN" bond. The purpose of forming the bridging structure is to prevent the electrostatic repulsion between the polar groups, thereby reducing the critical micelle concentration, that is, a smaller amount of addition can achieve better dispersion functional properties.
[0049] In some embodiments, when the flexible main chain is a polyether main chain, the twin-structure slurry additive has a structure shown in the following structural formula I:
[0050]
[0051] Among them, R1 is a C2-C5 alkane, 1-2 units of 1-methyl-2-ethylamine or an ether with 1-4 carbon atoms at both ends; R2 and R2' can be independently selected from any one of a polyethylene glycol structural unit, a polypropylene glycol structural unit, and a mixed unit of polyethylene glycol and polypropylene glycol, m is an integer of 0-20, n is an integer of 0-20, and 5≤m+n≤20; R3 and R3' can be independently selected from H or a C1-C3 alkane; R4 is at least one group selected from the group consisting of -NH2, -NHCO-CH3, -OH, Ar-OH, and -COOH.
[0052] As shown in Formula I, R1 is a C2-C5 alkane, 1-2 units of 1-methyl-2-ethylamine, or an ether with 1-4 carbon atoms at both ends. R1 is the middle junction position in the chain of the compound, and both ends of R1 are connected with nitrogen atoms to form an "NN" bond, forming a bridging structure to prevent electrostatic repulsion between polar groups, thereby reducing the critical micelle concentration, that is, a smaller amount of addition can achieve better dispersion functional properties.
[0053] R2 and R2' can be independently selected from any one of polyethylene glycol structural units, polypropylene glycol structural units, and mixed units of polyethylene glycol and polypropylene glycol, m is an integer of 0 to 20, n is an integer of 0 to 20, and 5≤m+n≤20. Polyethylene glycol and / or polypropylene glycol are used as the main chain of the twin-structure slurry additive, and the main chain formed is a hydrophilic flexible segment, which not only improves the water solubility of the molecule and the compatibility with the solvent, but also improves the flexibility of the material, plays a role in preventing cracking of thick coating, reduces coating energy consumption, improves slurry processability and increases slurry solid content.
[0054] In some embodiments, m and n can be selected from any one of 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, and 20. In addition, 5≤m+n≤20 is defined. In some embodiments, m+n can be any one of 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, and 20. The larger the total value of m+n, the larger the molecular weight of the twin-structure slurry additive, that is, the better the hydrophilicity, but the larger the molecular weight, the slower the migration speed in the solvent, which will affect the homogenization time and the overall performance of the product.
[0055] R3 and R3' may be independently selected from H or C1-C3 alkanes.
[0056] When R2 and R2' in Formula I are the same group, and R3 and R3' are the same group; the obtained polyether compound with a symmetrical structure has a high degree of symmetry and a regular lattice arrangement, and the symmetrical structure polyether chain has good solubility, dispersibility and processing performance. When R2 and R2' in Formula I are different groups, and R3 and R3' are the same group; or, R2 and R2' are the same group, and R3 and R3' are different groups; or, R2 and R2' are different groups, and R3 and R3' are different groups; the obtained polyether compound is a compound with an asymmetrical structure, and the groups of the asymmetrical structure polyether chain are irregularly arranged, and the properties and characteristics exhibited will vary depending on the specific structure.
[0057] R4 is at least one group selected from the group consisting of -NH2, -NHCO-CH3, -OH, Ar-OH, and -COOH. The provided group is a strong polar group, has a strong affinity with the positive electrode active material of the lithium ion battery, can be quickly and firmly adsorbed with the positive electrode active material, and can quickly and evenly gather on the surface of the positive electrode active material during the mixing process, thereby improving the overall dispersibility of the solution and reducing the viscosity.
[0058] In some embodiments, when the flexible main chain is a polyester main chain, the twin-structure slurry additive has a structure shown in the following structural formula II:
[0059]
[0060] The difference between Formula I and Formula II is that the main chain structures are different, but the types of branched functional groups are the same.
[0061] Wherein, R1 is a C2-C5 alkane, 1-2 units of 1-methyl-2-ethylamine or an ether having 1-4 carbon atoms at both ends; R4 is at least one group selected from the group consisting of -NH2, -NHCO-CH3, -OH, Ar-OH, and -COOH. The group selection of R1 and R4 is consistent with that shown in Formula I.
[0062] R5 and R5' can be independently selected from any one of poly(hexylene adipate) structural units, polycarbonate diol structural units, poly(butylene adipate) structural units, and polycaprolactone structural units, and 5≤p≤20, 5≤q≤20, |pq|≤2; R6 and R6' can be independently selected from H or an alkane chain of 1 to 3 carbons;
[0063] When R5 and R5' in Formula II are the same group, and R6 and R6' are the same group; the obtained polyester compound with a symmetrical structure has a high degree of symmetry and a regular lattice arrangement, and the symmetrical polyester chain has good solubility, dispersibility and processing performance. When R5 and R5' in Formula II are different groups, and R6 and R6' are the same group; or, R5 and R5' are the same group, and R6 and R6' are different groups; or, R5 and R5' are different groups, and R6 and R6' are different groups; the obtained polyester compound is a compound with an asymmetrical structure, and the groups of the asymmetrical polyester chain are irregularly arranged, and the properties and characteristics will vary depending on the specific structure.
[0064] In some embodiments, the weight average molecular weight of the twin-structure slurry additive is 1000 to 3000. It can be seen that the provided twin-structure slurry additive has a small molecular weight and a fast migration speed. The strong polar end in the additive can quickly and evenly gather on the surface of the carbon coating layer, quickly wet, and reduce the homogenization time. Compared with not adding a dispersant and adding a traditional dispersant, the slurry with the twin-structure slurry additive can obtain the desired slurry dispersion effect with a shorter stirring time, reducing the homogenization time cost, which is conducive to wide application.
[0065] In some embodiments, the second aspect of the present application provides a method for preparing a twin-structure slurry additive, comprising the following steps:
[0066] S01. Double-terminated amine compound H 2 N -R1- NH 2 and a flexible polymer compound containing an epoxy terminal group are mixed to perform a first ring-opening reaction, and then a purification treatment is performed to prepare a quasi-gemini structure solvated chain; wherein R1 is a C2-C5 alkane, 1-2 units of 1-methyl-2-ethylamine or an ether with 1-4 carbon atoms at both ends;
[0067] S02. Provide a small molecule compound, mix the small molecule compound with a twin-structure solvated chain, perform a second ring-opening reaction, and then perform purification treatment to prepare a twin-structure slurry additive, wherein the twin-structure slurry additive includes at least one group selected from the group consisting of -NH2, -NHCO-CH3, -OH, Ar-OH, and -COOH.
[0068] The second aspect of the embodiment of the present application provides a method for preparing a twin-structure slurry additive. The preparation method adopts a two-step process. First, a double-terminal amine compound is used to "bridge" and a flexible polymer compound containing an epoxy end group is subjected to a ring-opening reaction to prepare a bridging flexible twin-structure solvated chain; then the flexible twin-structure solvated chain is chemically reacted with a small molecule compound containing a strong polar head group to prepare a twin-structure slurry additive. The preparation method is simple, the reaction is mild, does not require the use of large-scale instruments and equipment, has low cost, and is easy to industrialize.
[0069] In step S01, the double-terminal amine compound H 2 N -R1— NH 2 and a flexible polymer compound containing an epoxy terminal group are mixed to perform a first ring-opening reaction, and then a purification treatment is performed to prepare a quasi-gemini structure solvated chain; wherein R1 is a C2-C5 alkane, 1-2 units of 1-methyl-2-ethylamine or an ether with 1-4 carbon atoms at both ends.
[0070] In some embodiments, since the double-terminal amine compound includes two amine groups for reaction, the molar ratio of the double-terminal amine compound to the flexible polymer compound containing epoxy terminal groups is 1:2.
[0071] In some embodiments, the double-terminal amine compound is H 2 N —R1— NH 2; wherein R1 is a C2-C5 alkane, 1-2 units of 1-methyl-2-ethylamine, or an ether having 1-4 carbon atoms at both ends. In some specific embodiments, the double-terminal amine compound is selected from any one of ethylenediamine, propylenediamine, diethylenetriamine, and 2,2'-oxybis(ethylamine).
[0072] In some embodiments, the flexible polymer compound containing epoxy terminal groups includes a polyether compound containing epoxy terminal groups or a polyester compound containing epoxy terminal groups.
[0073] In some embodiments, the polyether compound containing epoxy terminal groups is R2 and R2' can be independently selected from any one of polyethylene glycol structural units, polypropylene glycol structural units, and mixed units of polyethylene glycol and polypropylene glycol, m is an integer of 0 to 20, and n is an integer of 0 to 20; R3 and R3' can be independently selected from H or C1 to C3 alkanes.
[0074] In some specific embodiments, the polyether compound containing epoxy terminal groups is selected from epoxy terminal polyethylene glycol with a degree of polymerization of 10-20 or epoxy terminal polypropylene glycol with a degree of polymerization of 10-20.
[0075] In some embodiments, the polyester compound containing epoxy end groups is Wherein, R5 and R5' can be independently selected from any one of poly(hexylene adipate) structural unit, polycarbonate diol structural unit, poly(butylene adipate) structural unit and polycaprolactone structural unit, and 5≤p≤20, 5≤q≤20; R6 and R6' can be independently selected from H or an alkane chain of 1 to 3 carbons.
[0076] In some specific embodiments, the polyester compound containing epoxy terminal groups is selected from at least one of poly(hexylene adipate) with a degree of polymerization of 5 to 10, polycarbonate diol, poly(butylene adipate) and polycaprolactone.
[0077] In some embodiments, the entire preparation reaction is carried out under an inert gas atmosphere to ensure that there are no impurity molecules in the reaction process and that the product has a high purity. The inert gas includes but is not limited to nitrogen, helium, neon, argon, and krypton.
[0078] In some embodiments, the mixing further comprises: adding the double-terminal amine compound, the flexible polymer compound containing epoxy terminal groups and the catalyst into an organic solvent for a mixing reaction. The organic solvent includes but is not limited to at least one of methanol, ethanol, N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran and N-methylpyrrolidone.
[0079] In some embodiments, the temperature of the first ring-opening reaction is 60 to 80°C, and the time is 4 to 8 hours. In some specific embodiments, the temperature of the first ring-opening reaction includes but is not limited to 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C, 80°C. The time includes but is not limited to 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, and 8 hours. If the reaction temperature is too low or the reaction time is too short, the reaction is too slow; if the reaction temperature is too high or the time is too long, the reaction will be too violent.
[0080] Further, purification treatment is performed; the purification treatment can be performed by filtration, water washing, concentration, extraction, recrystallization, column chromatography and the like.
[0081] In some specific embodiments, the purification process includes the following steps: providing an extractant for repeated extraction, then washing with water, and collecting the organic phase; the organic phase is dried and evaporated under reduced pressure in turn to obtain a twin-like solvation chain. Among them, the extractant can be selected from organic solvents such as ethyl acetate, butyl acetate, chloroform, toluene, and the volume of the extractant is 1 / 5 to 1 / 3 of the volume of the extract. Under this condition, the organic phase can be extracted. The obtained organic phase is then dried, and the purpose of the drying process is mainly to remove moisture. It can be dried at room temperature for 1 to 2 hours; further, it is evaporated under reduced pressure for 5 to 6 hours at 0.8 to 0.9 atm and 60 to 80°C to obtain a purified twin-like solvation chain.
[0082] In step S02, a small molecule compound is provided, and the small molecule compound is mixed with a twin-structure solvated chain to perform a second ring-opening reaction, and then a purification treatment is performed to prepare a twin-structure slurry additive, wherein the twin-structure slurry additive includes at least one group selected from the group consisting of -NH2, -NHCO-CH3, -OH, Ar-OH, and -COOH.
[0083] In some embodiments, the small molecule compound has different anchoring groups, and the reactions with the twin-like solvation chain are also different. In some specific embodiments, a small molecule compound containing a hydroxyl group or a carboxylic acid is provided, which can be subjected to an amidation reaction to generate a phenol functional group; wherein, the amidation reaction requires an acidic catalyst, and the acidic catalyst is generally selected from any one of sulfuric acid, formic acid, ammonium chloride, and 4-dimethylaminopyridine. In some specific embodiments, a small molecule compound containing an amide group is provided, which can be subjected to a Michael addition reaction to generate an amide functional group; wherein, the Michael addition reaction requires a basic catalyst, and the basic catalyst is generally selected from any one of sodium hydroxide, potassium hydroxide, sodium ethoxide, sodium hydride, and sodium amide. In some specific embodiments, a small molecule compound containing an epoxy group is provided, and the epoxy can react with the secondary amine in the amine group to generate a hydroxyl functional group. In some specific embodiments, a small molecule compound containing an amine group or a carboxyl group is provided, and then the amine group or the carboxyl group is directly introduced through an addition reaction.
[0084] In some embodiments, the small molecule compound is selected from any one of p-hydroxybenzoic acid, 3,4-dihydroxybenzoic acid, 3,4,5-trihydroxybenzoic acid, acrylamide, acrylamide, propylene oxide, and methyl acrylate. Among them, p-hydroxybenzoic acid, 3,4-dihydroxybenzoic acid, and 3,4,5-trihydroxybenzoic acid can undergo amidation reaction to generate phenol functional groups; acrylamide and acrylamide can undergo Michael addition reaction to generate amide functional groups; propylene oxide participates in the reaction, that is, epoxy reacts with secondary amine to generate hydroxyl functional groups; acrylamide can undergo Michael addition reaction to generate carboxyl functional groups.
[0085] In some embodiments, the small molecule compound and the twin-like solvated chain are mixed with an organic solvent and then subjected to a second ring-opening reaction. The anchoring site is determined according to the group of the small molecule compound, and the added molar amount is determined according to the number of anchoring points. The organic solvent includes but is not limited to at least one of methanol, ethanol, N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, and N-methylpyrrolidone. In the specific implementation process, step S01 and step S02 use the same organic solvent for dissolution reaction.
[0086] In some embodiments, the temperature of the second ring-opening reaction is 23 to 25°C, and the time is 3 to 6 hours. In some specific embodiments, the temperature of the second ring-opening reaction includes but is not limited to 23°C, 23.5°C, 24°C, 24.5°C, and 25°C. The time is but is not limited to 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, and 6 hours. If the reaction temperature is too low or the reaction time is too short, the reaction is too slow; if the reaction temperature is too high or the time is too long, the reaction will be too violent.
[0087] Further, purification treatment is performed; the purification treatment can be performed by filtration, water washing, concentration, extraction, recrystallization, column chromatography and the like.
[0088] In some specific embodiments, the purification process includes the following steps: providing an extractant for repeated extraction, then washing with water, collecting an organic phase; and sequentially drying and evaporating the organic phase under reduced pressure to obtain a twin-like structure slurry additive. The specific operation method of the purification process is consistent with the treatment method of step S01.
[0089] A third aspect of an embodiment of the present application provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode film layer located on at least one surface of the positive electrode current collector, wherein the positive electrode film layer is obtained by coating a positive electrode slurry, wherein the positive electrode slurry comprises the above-mentioned twin-like structure slurry additive or a positive electrode slurry prepared according to the above-mentioned method for preparing the twin-like structure slurry additive.
[0090] A third aspect of an embodiment of the present application provides a positive electrode plate, which includes a positive electrode collector and a positive electrode film layer located on at least one surface of the positive electrode collector, wherein the positive electrode film layer is obtained by coating a positive electrode slurry, wherein applying the above-mentioned twin-structure slurry additive to the positive electrode slurry is beneficial to reducing the viscosity of the positive electrode slurry and improving the dispersibility of the positive electrode slurry, while being able to reduce the aggregation of the positive electrode active material in the positive electrode slurry, improve the performance of the positive electrode slurry, and make the obtained positive electrode slurry have a good dispersion effect, so that the positive electrode active material in the positive electrode slurry is evenly dispersed on the surface of the positive electrode plate, while preventing cracking, reducing the coating time, and improving efficiency.
[0091] In some embodiments, based on the total mass of the positive electrode slurry, the mass content of the quasi-twin structure slurry additive is 0.05% to 0.3%. In some specific embodiments, based on the total mass of the positive electrode slurry, the mass content of the quasi-twin structure slurry additive includes but is not limited to 0.05%, 0.06%, 0.08%, 0.1%, 0.12%, 0.14%, 0.16%, 0.18%, 0.20%, 0.22%, 0.24%, 0.26%, 0.28%, 0.3%. Since the provided quasi-twin structure slurry additive has excellent dispersibility and flexibility, and the concentration of the quasi-twin structure forming micelles in the additive is low, the added amount is lower, and the effect of high addition of traditional polymer dispersants can be achieved. At the same time, the content of the provided twin-structure slurry additive in the positive electrode slurry is controlled within the above-mentioned range, which can make the positive electrode slurry have good conductivity, and at the same time can greatly improve the viscosity of the positive electrode material, so that it has good processing performance, and can improve the dispersion uniformity of the positive electrode slurry during the preparation of the positive electrode sheet, so that the secondary battery has a higher capacity and improved cycle performance.
[0092] In some embodiments, the twin-like structure slurry additive provided above is applied to the positive electrode slurry, and the homogenization time of the obtained positive electrode slurry is controlled to be 7 to 15 minutes, so that the slurry with excellent fluidity can be obtained for use. Compared with adding traditional functional additives, the homogenization time can be reduced by more than 50% to ensure that the slurry with the same fluidity is achieved.
[0093] In some embodiments, the obtained positive electrode sheet density is ≥21 mg / cm 2 , the flexibility is improved by 5% to 9%. It can be seen that the obtained positive electrode plate adopts the positive electrode slurry additive containing the above-mentioned positive electrode slurry additive. The positive electrode slurry additive contains medium and low polarity polyether chains, which greatly improves the flexibility and material density, and does not affect the peel strength and resistivity of the plate within the addition amount range, and will not affect the electrochemical performance of the battery.
[0094] The positive electrode slurry provided also includes positive electrode active materials, conductive agents, and adhesives. The positive electrode active materials include but are not limited to any one of LiFePO4, LiCoO2, and LiNiO2; the conductive agents include but are not limited to any one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, and carbon nanofibers; and the adhesives include but are not limited to any one of polyvinylidene fluoride, polytetrafluoroethylene, and fluorine-containing acrylate resins.
[0095] The current collector provided includes but is not limited to any one of aluminum foil, nickel mesh or aluminum-plastic composite film.
[0096] A fourth aspect of an embodiment of the present application provides a secondary battery, the secondary battery comprising a positive electrode plate.
[0097] A fourth aspect of an embodiment of the present application provides a secondary battery, which includes the above-mentioned positive electrode plate. The obtained secondary battery has excellent cycle performance and specific capacity, and is conducive to wide application.
[0098] Among them, the secondary battery includes a positive electrode and a negative electrode electrolyte, the positive electrode and the negative electrode are arranged in the electrolyte, and the negative electrode includes the negative electrode plate provided in the above embodiment. Optionally, the electrolyte includes a liquid electrolyte or a solid electrolyte. If a liquid electrolyte is selected, a diaphragm must also be included. During the battery charge and discharge process, the active positive electrode ions are embedded and removed back and forth between the positive electrode and the negative electrode. The electrolyte plays a role in conducting positive electrode ions between the positive electrode and the negative electrode. The diaphragm is arranged between the positive electrode and the negative electrode, mainly to prevent the positive and negative electrodes from short-circuiting, and at the same time allow the positive electrode ions to pass through.
[0099] The following describes the invention in conjunction with specific embodiments.
[0100] Example A1
[0101] Quasi-gemini structure slurry additive and preparation method thereof
[0102] The twin-structure slurry additive is shown in the following formula - Example 1:
[0103] n is 10.
[0104] The preparation method of the twin-structure slurry additive comprises the following steps:
[0105] (1) Preparation of Gemini-like solvated chains. Specifically, 0.2 mol of ethylenediamine and 0.4 mol of epoxy-terminated polyether (n=10) 0.4 mol KOH was added to the DMSO (300 mL) solution. The reaction mixture was stirred at 80°C for 6 h under nitrogen protection, then extracted with ethyl acetate and washed with water. After separation, the organic phase was dried over MgSO4 and evaporated under reduced pressure to obtain a purified twin-like solvated chain.
[0106] (2) Preparation of Gemini-like slurry additive. A solution of Gemini-like solvated chain (0.1 mol), 3,4-dihydroxybenzoic acid (0.2 mol), formic acid catalyst (0.01 mol), and tetrahydrofuran (150 mL) was prepared. The reaction mixture was stirred at room temperature for 5 hours under nitrogen protection, extracted with ethyl acetate, washed with water, dried with MgSO4, and evaporated under reduced pressure. The dried reaction product was dispersed in an organic polar solvent, extracted with ethyl acetate for multiple times, washed with water, and evaporated under reduced pressure to obtain a Gemini-like slurry additive.
[0107] Example A2
[0108] Quasi-gemini structure slurry additive and preparation method thereof
[0109] The twin-structure slurry additive is shown in the following formula - Example 2:
[0110] n=10.
[0111] Compared with Example A1, the preparation method of the twin-structure slurry additive is modified by replacing "3,4-dihydroxybenzoic acid (0.2 mol), formic acid catalyst (0.01 mol)" in step (2) with "ethylene oxide (0.2 mol)"; the other steps are the same.
[0112] Example A3
[0113] Quasi-gemini structure slurry additive and preparation method thereof
[0114] The twin-structure slurry additive is shown in the following formula - Example 3:
[0115] n=10.
[0116] Compared with Example A1, the preparation method of the twin-structure slurry additive is modified from "3,4-dihydroxybenzoic acid (0.2 mol), formic acid catalyst (0.01 mol)" in step (2) to "acrylamide (0.2 mol), ethanol catalyst (0.01 mol)"; the other steps are the same.
[0117] Example A4
[0118] Quasi-gemini structure slurry additive and preparation method thereof
[0119] The twin-structure slurry additive is shown in the following formula - Example 4:
[0120] n=10.
[0121] Compared with Example A1, the preparation method of the twin-structure slurry additive is modified by changing the "3,4-dihydroxybenzoic acid (0.2 mol), formic acid catalyst (0.01 mol)" in step (2) to "methyl acrylate (0.2 mol), sodium ethoxide catalyst (0.01 mol)"; in step (2), after reacting for 5 hours, a supplementary step is added: "Add an appropriate amount of sodium hydroxide to adjust the pH of the solution to 10, and hydrolyze the ester for 2 hours to obtain a carboxylate. Add HCl / H2SO4 to adjust the pH of the solution to 1.0, and reduce the carboxylate to a carboxyl group." The other steps are the same.
[0122] Example A5
[0123] Quasi-gemini structure slurry additive and preparation method thereof
[0124] The twin-structure slurry additive is shown in the following formula - Example 5:
[0125] n=10.
[0126] Compared with Example A1, the preparation method of the twin-structure slurry additive is as follows: "ethylenediamine" in step (1) is changed to "diethylenetriamine"; and "the amount of 3,4-dihydroxybenzoic acid (0.2 mol) in step (2) is adjusted to 0.3 mol". The other steps are the same.
[0127] Example A6
[0128] Quasi-gemini structure slurry additive and preparation method thereof
[0129] The twin-structure slurry additive is shown in the following formula - Example 6:
[0130] m=10, n=11.
[0131] The preparation method of the twin-structure slurry additive comprises the following steps:
[0132] (1) Preparation of Gemini-like solvated chains. Specifically, 0.2 mol of ethylenediamine and 0.4 mol of epoxy-terminated polyether, wherein 0.2 mol of the polyether has a degree of polymerization of 10 and the other 0.2 mol of the polyether has a degree of polymerization of 11. 0.4 mol of KOH was added to a DMSO (300 mL) solution. The reaction mixture was stirred at 80° C. for 6 h under nitrogen protection, then extracted with ethyl acetate and washed with water. After stratification, the organic phase was dried over MgSO4 and evaporated under reduced pressure to obtain a purified Gemini-like solvated chain.
[0133] (2) Preparation of Gemini-like slurry additive. A solution of Gemini-like solvated chain (0.1 mol), 3,4-dihydroxybenzoic acid (0.2 mol), formic acid catalyst (0.01 mol), and tetrahydrofuran (150 mL) was prepared. The reaction mixture was stirred at room temperature for 5 hours under nitrogen protection, extracted with ethyl acetate, washed with water, dried with MgSO4, and evaporated under reduced pressure. The dried reaction product was dispersed in an organic polar solvent, extracted with ethyl acetate for multiple times, washed with water, and evaporated under reduced pressure to obtain a Gemini-like slurry additive.
[0134] Example A7
[0135] Quasi-gemini structure slurry additive and preparation method thereof
[0136] The twin-structure slurry additive is shown in the following formula - Example 7:
[0137] n=10.
[0138] The preparation method of the twin-structure slurry additive comprises the following steps:
[0139] (1) Preparation of Gemini-like solvated chains. Specifically, 0.2 mol of ethylenediamine and 0.4 mol of epoxy-terminated polycaprolactone, wherein the degree of polymerization of the epoxy-terminated polycaprolactone is 10. 0.4 mol of KOH was added to a DMSO (300 mL) solution. The reaction mixture was stirred at 80° C. for 6 h under nitrogen protection, then extracted with ethyl acetate and washed with water. After stratification, the organic phase was dried over MgSO4 and evaporated under reduced pressure to obtain a purified Gemini-like solvated chain.
[0140] (2) Preparation of Gemini-like slurry additive. A solution of Gemini-like solvated chain (0.1 mol), 3,4-dihydroxybenzoic acid (0.2 mol), formic acid catalyst (0.01 mol), and tetrahydrofuran (150 mL) was prepared. The reaction mixture was stirred at room temperature for 5 hours under nitrogen protection, extracted with ethyl acetate, washed with water, dried with MgSO4, and evaporated under reduced pressure. The dried reaction product was dispersed in an organic polar solvent, extracted with ethyl acetate for multiple times, washed with water, and evaporated under reduced pressure to obtain a Gemini-like slurry additive.
[0141] Example A8
[0142] Quasi-gemini structure slurry additive and preparation method thereof
[0143] The twin-structure slurry additive is shown in the following formula - Example 8:
[0144] m=10, n=9.
[0145] The preparation method of the twin-structure slurry additive comprises the following steps:
[0146] (1) Preparation of Gemini-like solvated chains. Specifically, 0.2 mol of ethylenediamine and 0.4 mol of epoxy-terminated polycaprolactone, wherein 0.2 mol of the polycaprolactone has a degree of polymerization of 10 and the other 0.2 mol has a degree of polymerization of 9. 0.4 mol of KOH was added to a DMSO (300 mL) solution. The reaction mixture was stirred at 80° C. for 6 h under nitrogen protection, then extracted with ethyl acetate and washed with water. After stratification, the organic phase was dried over MgSO4 and evaporated under reduced pressure to obtain a purified Gemini-like solvated chain.
[0147] (2) Preparation of Gemini-like slurry additive. A solution of Gemini-like solvated chain (0.1 mol), 3,4-dihydroxybenzoic acid (0.2 mol), formic acid catalyst (0.01 mol), and tetrahydrofuran (150 mL) was prepared. The reaction mixture was stirred at room temperature for 5 hours under nitrogen protection, extracted with ethyl acetate, washed with water, dried with MgSO4, and evaporated under reduced pressure. The dried reaction product was dispersed in an organic polar solvent, extracted with ethyl acetate for multiple times, washed with water, and evaporated under reduced pressure to obtain a Gemini-like slurry additive.
[0148] Comparative Example A1
[0149] Additive and preparation method thereof
[0150] An additive is directly provided, and the additive is N-methylpyrrolidone.
[0151] Comparative Example A2
[0152] A dispersant is directly provided, and the dispersant is PVP-K15 (polyvinyl pyrrolidone K-15).
[0153] Comparative Example A3
[0154] A dispersant is directly provided, and the dispersant is PVB (polyvinyl formal, with a molecular weight Mw of 10000-15000).
[0155] Comparative Example A4
[0156] Additive and preparation method thereof
[0157] The additive is shown in the following formula - Comparative Example A4:
[0158] n=10.
[0159] Compared with Example A1, the preparation method of the additive does not contain step (2).
[0160] Example B1
[0161] Positive electrode slurry and preparation method thereof
[0162] The positive electrode active material lithium iron phosphate (LFP), the binder polyvinylidene fluoride (PVDF), the conductive agent carbon black (SP), and the solvent N-methylpyrrolidone (NMP) were added into a stirring tank for stirring and mixing to obtain a positive electrode slurry. The total mass of the provided positive electrode slurry was 100%, and the mass content of the quasi-gemini structure slurry additive prepared in Example A1 was added in an amount of 0.05%, and then the slurry was homogenized and mixed using a degassing machine. The homogenization mixing process was: 600 rpm dispersion for 30 s, 2000 rpm dispersion for X (6.5 / 7.5 / 15 / 20 / 24 / 25) min. The positive electrode slurry was obtained.
[0163] The composition and preparation method of the positive electrode slurry of Example B2 to Example B8 are consistent with Example B1, and the "quasi-twin structure slurry additive prepared in Example A1" is used corresponding to the "quasi-twin structure slurry additive prepared in Example A2 to Example A8".
[0164] The composition and preparation method of the positive electrode slurry of Comparative Examples B1 to B4 are consistent with those of Example B1, and the "gemini-structure slurry additive prepared in Example A1" is used corresponding to the "additive provided by Comparative Examples A1 to A4".
[0165] Performance Testing
[0166] 1. Test the properties of Example B1 to Example B8 and Comparative Example B1 to Comparative Example B4.
[0167] The specific properties are shown in Table 1, which mainly analyzes the solid content, homogenization time, discharge viscosity, discharge fluidity, 24-hour viscosity, 24-hour fluidity and other properties of the slurry after adding different additives. In terms of solid content, the positive electrode slurry prepared by using the twin-structure slurry additive provided by the present application has a solid content of more than 63.5% when the addition amount is only 0.05%, while the additive addition amount provided in the comparative example is 0.1%, and the solid content is 57% to 61%. It can be seen that the positive electrode slurry added with the twin-structure slurry additive provided by the present application can obtain a higher solid content by adding a smaller amount. At the same time, it can be compared that the overall solid content is increased by at least 2.5% to 8%, and the processing performance is improved.
[0168] Among them, the physical sample of the slurry obtained is as follows Figure 1 As shown, Figure 1 A, after being lifted evenly with a medicine spoon and tilted naturally at 10-30 degrees, the fluid flows naturally, which means that the slurry has good fluidity; Figure 1 B, after being lifted evenly with a medicine spoon and naturally tilted 10-30 degrees, the fluid flows naturally but is interrupted, which means that the fluidity of the slurry is normal; Figure 1 If the fluid does not drip after being evenly lifted up with a medicine spoon and naturally tilted at 10-30 degrees, it means that the slurry has poor fluidity.
[0169] In the actual processing process, the positive electrode slurry prepared by using the twin-structure slurry additive provided in the present application can generally be completed in 7.5 minutes, or even in 6.5 minutes, and the obtained slurry has good fluidity and low viscosity, both lower than 10550mPa·s. After 24 hours of placement, the slurry fluidity is still good and the viscosity is still low, with little difference, and the stability is excellent; while when the additive provided in the comparative example is used to prepare the slurry, if the homogenization time is 7.5 minutes, the fluidity of the obtained slurry is mostly poor, and only when the homogenization time reaches more than 15 minutes, the fluidity of the obtained slurry is general or good, but the viscosity is high, both higher than 10840mPa·s; after 24 hours of placement, the slurry fluidity deteriorates and the viscosity increases after 24 hours, which is not conducive to use. Therefore, applying the above-mentioned twin-structure slurry additive to the positive electrode slurry is beneficial to reducing the viscosity of the positive electrode slurry and improving the dispersibility of the positive electrode slurry. At the same time, it can reduce the aggregation of the positive electrode active material in the positive electrode slurry and improve the performance of the positive electrode slurry, so that the obtained positive electrode slurry has a good dispersion effect and improves the overall performance.
[0170] Table 1
[0171]
[0172] 2. Infrared spectrum performance analysis
[0173] The twin-structure slurry additive obtained in Example A1 was subjected to infrared spectroscopy analysis. Figure 2 As shown, P1 (3459cm -1 ) corresponds to the stretching vibration absorption peak of the hydroxyl group on the benzene ring and the hydroxyl group on the solvated chain; P2 (2860cm -1 and 2925cm -1 ) corresponds to the CH stretching vibration absorption peak of the solvated chain; P3 (1738cm -1 ) corresponds to the characteristic stretching vibration peak of the carbonyl C=O of the amide group, while the amine N(R)2 of the amide group has no absorption peak because it does not contain hydrogen; P4 (1403cm -1 ) corresponds to the C=C stretching vibration peak of the benzene ring on the polar group; P5 (1093cm -1 ) corresponds to the vibration peak of COC on the solvation chain.
[0174] 3. Electrochemical performance test
[0175] The positive electrode slurries in the embodiments and comparative examples were applied to lithium-ion secondary batteries for performance testing.
[0176] (1) Preparation of positive electrode sheet
[0177] The positive electrode slurry obtained in each embodiment and comparative example was uniformly coated on the positive electrode current collector (aluminum foil), dried at 120°C for 12h, and a positive electrode sheet was prepared. The properties of the positive electrode sheet were tested, as shown in Table 2. Among them, the homogenization time in the positive electrode slurry preparation process used in the embodiment is mostly only 7.5 minutes, and some embodiments even complete the homogenization at 6.5 minutes, and the obtained slurry has good discharge fluidity, and the discharge viscosity is lower than 10550mPa·s; while the slurry of the comparative example was observed during the preparation process after the homogenization time was 20 minutes, and the discharge fluidity of the slurry was generally good, and the discharge viscosity was lower than 11560mPa·s, so the slurry of the comparative example needs a homogenization time of at least 20 minutes. It can be seen that the time used in the process of preparing the slurry using the twin-structure slurry additive provided in the present application is shorter, more time-saving, and a slurry with better dispersibility can be obtained in a shorter time. The positive electrode slurry is coated on the surface of the current collector. Since the positive electrode slurry provided contains the above-prepared twin-structure slurry additive, the additive has the function of defoaming and suppressing foaming. Therefore, there are no bubbles and pits on the surface of the pole piece obtained in the embodiment, and the surface is smooth. In addition, the density of the pole piece is ≥21 mg / cm 2 , resistivity ≤11.8Ω·cm, pole piece peeling force ≤0.075mN·mm; while the pole pieces obtained in the comparative example all have pores and pits, and the pole piece density ≤20mg / cm 2 , resistivity ≥ 11.2Ω·cm, pole piece peeling force ≤ 0.072mN·mm; it can be seen that the additive in the positive electrode slurry obtained in the embodiment greatly improves the flexibility and material density due to the presence of medium and low polarity polyether chains, but does not affect the peeling strength and resistivity of the pole piece within the range of the added amount, and does not affect the electrochemical performance of the battery.
[0178] Table 2
[0179]
[0180]
[0181] (2) Preparation of secondary batteries
[0182] The positive electrode sheet obtained from the positive electrode slurry obtained in each embodiment and comparative example is used as the positive electrode sheet, the lithium sheet is used as the negative electrode, the polypropylene microporous membrane is used as the diaphragm, the diaphragm thickness is 12μm, the electrolyte is 1mol / L LiPF6, and the electrolyte is ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a volume ratio of 1:1:1. The button batteries are assembled in a glove box. The button batteries prepared are tested at 25°C for 1C charging capacity, 1C discharge capacity, and first cycle charge and discharge efficiency, as shown in Table 3. Among them, the homogenization time represents the start of the homogenization, and the timing is stopped when the slurry discharge flow is in a good state or above;
[0183] Table 3
[0184]
[0185] By comparing the batteries of the embodiment and the comparative example, it can be found that the homogenization time in the preparation process of the positive electrode slurry used in the embodiment is only 7.5 minutes, especially the embodiment B6 can reach a good state in 6.5 minutes, while the homogenization time of the slurry in the comparative example is 20 minutes or even 25 minutes. It can be seen that the time used in the slurry preparation process using the twin-structure slurry additive provided by the present application is shorter and more time-saving. The secondary battery assembled with the positive electrode sheet prepared by the additive of the embodiment has a first charge capacity higher than 162.9mAh / g, a 1C rate capacity higher than 136.2mAh / g, and a cycle rate higher than 93.1%; while the secondary battery assembled with the positive electrode sheet prepared by the additive provided in the comparative example has a first charge capacity only higher than 160.8mAh / g, a 1C rate capacity higher than 132.7mAh / g, and a cycle rate higher than 91.1%.
[0186] like Figure 3 As shown, Example B1, Example B6, Comparative Example B2 and Comparative Example B4 are specifically analyzed. The 1C rate capacity of Example B1 is 136.2 mAh / g, and the capacity retention rate of 1C cycle 500 cycles is 93.2%; the 1C rate capacity of Example B6 is 136.8 mAh / g, and the capacity retention rate of 1C cycle 500 cycles is 93.8%; the 1C rate capacity of Comparative Example B2 is 134.5 mAh / g, and the capacity retention rate of 1C cycle 500 cycles is 91.8%; the 1C rate capacity of Comparative Example B4 is 136.5 mAh / g, and the capacity retention rate of 1C cycle 500 cycles is 93.3%; It can be seen that the performance of the battery of Comparative Example B4 is close to that of Example B1 and Example B6, which may be due to the fact that the additive of Comparative Example A4 provided has a flexible main chain, and the flexible main chain has good compatibility with the solvent in the slurry, and can form a stable emulsified system, so it has similar excellent cycle performance and specific capacity as the embodiments. However, the additive of Comparative Example A4 does not include an anchoring group. As can be seen from Table 3, the homogenization time of Comparative Example B4 is very long, and it takes 24 minutes to obtain a slurry with good fluidity.
[0187] It can be seen that the secondary battery assembled by assembling the positive electrode plate prepared by using the additives of the embodiment has a shorter slurry homogenization time during the preparation process and can have excellent cycle performance and specific capacity; while in the battery of the comparative example, the additives provided by the embodiments of the present application are not added to the positive electrode slurry, the slurry homogenization time is long, and the obtained electrode plate surface will have problems such as bubbles and depressions, resulting in reduced electrode plate quality, and further resulting in battery capacity loss and reduced cycle performance. In addition, since polymer materials are introduced into the positive electrode slurry, the electrode plate resistivity will increase and the capacity will further decrease, thereby resulting in a decrease in cycle performance.
[0188] In summary, the twin-structure slurry additive provided in the embodiments of the present application includes at least one low-polarity flexible main chain and a strong polar head group connected to the flexible main chain by a covalent bond, wherein the strong polar head group can better adsorb the high-polarity components in the slurry, firmly anchor with it, play a role of steric hindrance, and significantly improve the overall dispersibility of the slurry; the low-polarity flexible main chain has good compatibility with the solvent in the slurry, and can form a stable emulsified system, which is conducive to better stabilizing the particles in the slurry and avoiding the aggregation and sedimentation of the slurry. The main chain has excellent flexibility and avoids the problem of cracking when the slurry is thickly coated; and multiple flexible main chains can be connected by a bridging structure. The bridge structure used can prevent the electrostatic repulsion between the polar groups, so that they are more closely arranged on the surface of the slurry particles, thereby reducing the critical micelle concentration, that is, a smaller addition amount can play a better dispersing functional characteristic. This type of twin-structure slurry additive is used in battery slurry, has excellent compatibility with the slurry, is conducive to improving the dispersion effect, and can improve the flexibility of the slurry, and can be widely used.
[0189] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A twin-structure slurry additive, characterized in that: The twin-like structure slurry additive comprises at least one low-polarity flexible main chain and a strong-polarity head group connected to the flexible main chain by covalent bonds, wherein the flexible main chain comprises a bridging structure.
2. The twin-structure slurry additive according to claim 1, characterized in that: The flexible main chain comprises a polyether main chain or a polyester main chain; and / or, The bridging structure includes an "NN" bond.
3. The twin-structure slurry additive according to claim 2, characterized in that: When the flexible main chain is a polyether main chain, the twin-structure slurry additive has a structure shown in the following structural formula I: Wherein, R1 is a C2-C5 alkane, 1-2 units of 1-methyl-2-ethylamine or an ether with 1-4 carbon atoms at both ends; R2 and R2' can be independently selected from any one of a polyethylene glycol structural unit, a polypropylene glycol structural unit, and a mixed unit of polyethylene glycol and polypropylene glycol, m is an integer of 0-20, n is an integer of 0-20, and 5≤m+n≤20; R3 and R3' can be independently selected from H or a C1-C3 alkane; R4 is at least one group selected from the group consisting of -NH2, -NHCO-CH3, -OH, Ar-OH, and -COOH; When the flexible main chain is a polyester main chain, the twin-structure slurry additive has a structure shown in the following structural formula II: Among them, R1 is a C2-C5 alkane, 1-2 units of 1-methyl-2-ethylamine or an ether with 1-4 carbon atoms at both ends; R4 is at least one group selected from the group consisting of -NH2, -NHCO-CH3, -OH, Ar-OH, and -COOH; R5 and R5' can be independently selected from any one of poly(hexylene adipate) structural units, polycarbonate diol structural units, poly(butylene adipate) structural units, and polycaprolactone structural units, and 5≤p≤20, 5≤q≤20, and |pq|≤2; R6 and R6' can be independently selected from H or an alkane chain with 1 to 3 carbon atoms.
4. The twin-structure slurry additive according to claim 1, characterized in that: The weight average molecular weight of the twin-structure slurry additive is 1000-3000.
5. A method for preparing a twin-structure slurry additive, characterized in that: The steps include: A double-terminal amine compound H2N-R1-NH2 and a flexible polymer compound containing an epoxy terminal group are mixed and subjected to a first ring-opening reaction, followed by purification treatment to prepare a quasi-gemini structure solvated chain; wherein R1 is a C2-C5 alkane, 1-2 units of 1-methyl-2-ethylamine, or an ether having 1-4 carbon atoms at the double terminals; A small molecule compound is provided, the small molecule compound is mixed with a twin-structure solvated chain, a second ring-opening reaction is performed, and then a purification treatment is performed to prepare a twin-structure slurry additive, wherein the twin-structure slurry additive includes at least one group selected from the group consisting of -NH2, -NHCO-CH3, -OH, Ar-OH, and -COOH.
6. The method for preparing the twin-structure slurry additive according to claim 5, characterized in that: The flexible polymer compound containing epoxy terminal groups includes a polyether compound containing epoxy terminal groups or a polyester compound containing epoxy terminal groups; Wherein, the polyether compound containing epoxy terminal groups is Wherein, R2 and R2' can be independently selected from any one of polyethylene glycol structural units, polypropylene glycol structural units, and mixed units of polyethylene glycol and polypropylene glycol, m is an integer of 0 to 20, and n is an integer of 0 to 20; R3 and R3' can be independently selected from H or C1 to C3 alkanes; The polyester compound containing epoxy terminal groups is Wherein, R5 and R5' can be independently selected from any one of poly(hexylene adipate) structural unit, polycarbonate diol structural unit, poly(butylene adipate) structural unit and polycaprolactone structural unit, and 5≤p≤20, 5≤q≤20; R6 and R6' can be independently selected from H or an alkane chain of 1 to 3 carbons.
7. The method for preparing the twin-structure slurry additive according to claim 5, characterized in that: The temperature of the first ring-opening reaction is 60 to 80° C. and the time is 4 to 8 hours; and / or, The temperature of the second ring-opening reaction is 23-25° C., and the time is 3-6 hours.
8. The method for preparing the twin-structure slurry additive according to claim 5, characterized in that: The double-terminal amine compound is selected from ethylenediamine, propylenediamine, diethylenetriamine, 2,2'-oxybis(ethylamine); and / or, The small molecule compound is selected from any one of p-hydroxybenzoic acid, 3,4-dihydroxybenzoic acid, 3,4,5-trihydroxybenzoic acid, acrylamide, acrylformamide, propylene oxide, and methyl acrylate; and / or, The flexible polymer compound containing epoxy terminal groups is selected from at least one of epoxy terminal polyethylene glycol with a polymerization degree of 10 to 20, epoxy terminal polypropylene glycol with a polymerization degree of 10 to 20, poly(hexylene adipate) with a polymerization degree of 5 to 10, polycarbonate diol, poly(butylene adipate) and polycaprolactone.
9. A positive electrode sheet, characterized in that: The positive electrode plate includes a positive electrode current collector and a positive electrode film layer located on at least one surface of the positive electrode current collector, wherein the positive electrode film layer is obtained by coating a positive electrode slurry, wherein the positive electrode slurry includes the twin-structure slurry additive described in any one of claims 1 to 4 or the positive electrode slurry prepared according to the preparation method of the twin-structure slurry additive described in any one of claims 5 to 8.
10. A secondary battery, characterized in that: Comprising a positive electrode, a negative electrode and an electrolyte, the secondary battery comprises the positive electrode sheet according to claim 9.